1996
DOI: 10.1116/1.580342
|View full text |Cite
|
Sign up to set email alerts
|

Role of surface stoichiometry in the Cl2/GaAs(001) reaction

Abstract: The room-temperature reaction of Cl 2 with GaAs͑001͒-4ϫ6,-c(2ϫ8), and-c(4ϫ4) surfaces is studied with synchrotron soft x-ray photoelectron spectroscopy. The chemical composition of the reacted surfaces is found to depend on the stoichiometry of the starting surface. In all cases, the reaction occurs stepwise, with Ga and As monochlorides formed prior to the dichlorides. The Ga-rich surface is initially more reactive than either of the As-rich surfaces and it forms more GaCl than the As-rich surfaces, which ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…Furthermore, the film growth method should be a simple, inexpensive chemical process that is similar in procedure to SiO 2 growth on Si via exposure to O 2 . Recently, it was shown that a 10 eV band gap insulator, GaF 3 , can be grown on GaAs via exposure to various fluorine-based compounds (30,34,35,38,107,108,120,(123)(124)(125)(126). Operational devices have been constructed from GaF 3 -GaAs structures (124,125,(127)(128)(129), which demonstrates that the interface state density can be reduced to a sufficiently low level that GaF 3 may be a suitable insulator for GaAs-based devices.…”
Section: Fluorinementioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the film growth method should be a simple, inexpensive chemical process that is similar in procedure to SiO 2 growth on Si via exposure to O 2 . Recently, it was shown that a 10 eV band gap insulator, GaF 3 , can be grown on GaAs via exposure to various fluorine-based compounds (30,34,35,38,107,108,120,(123)(124)(125)(126). Operational devices have been constructed from GaF 3 -GaAs structures (124,125,(127)(128)(129), which demonstrates that the interface state density can be reduced to a sufficiently low level that GaF 3 may be a suitable insulator for GaAs-based devices.…”
Section: Fluorinementioning
confidence: 99%
“…Thus, chlorine simply bonds to whichever element is present at the surface. Mokler et al (138), using thermal desorption spectroscopy (TDS) and AES, and Simpson et al (120), using SXPS, found that the initial rate of Cl uptake is greater on Ga-rich surfaces. Mokler et al (138) further showed that a surface capped with 50Å of As was entirely unreactive to Cl 2 .…”
Section: Chlorinementioning
confidence: 99%
See 3 more Smart Citations